Family and Non-Family Businesses in Iran: Coupling among Innovation, Internationalization and Growth-Expectation - Samsami, Mahsa; Schøtt, Thomas (European Journal of Family Business, 2021)
Gallo and Sveen, in 1991, specified problems of whether family businesses can take advantage of factors facilitating internationalization. We compare family and non-family businesses in innovation, export, and growth-expectation, and consider how outcomes are aligned, with a coupling that may be loose, with a synergy that benefits the business. This raises a further issue, is governance of a business affecting not only each of the outcomes but also their coupling. A representative sample of 530 Iranian businesses was surveyed in 2018 for Global Entrepreneurship Monitor. Innovation, export, and growth-expectation are found to be lower in family businesses. Coupling between innovation and export, and also between export and growth-expectation, are found to be looser in family businesses. - Findings suggest that coupling among performance outcomes in family businesses can feasibly be tightened, thereby reinforcing performance. The findings contribute to understanding the performance endeavors of family businesses as problematized by Gallo and Sveen.